2019
DOI: 10.1007/s00394-019-02037-x
|View full text |Cite
|
Sign up to set email alerts
|

Iodine status of teenage girls on the island of Ireland

Abstract: The trace element iodine is a vital constituent of thyroid hormones. Iodine requirements increase during pregnancy, when even mild deficiency may affect the neurocognitive development of the offspring. Urinary iodine concentration (UIC) is the means of assessing iodine status in population surveys; a median UIC of 100-199 µg/L is deemed sufficient in a non-pregnant population. Milk is the main dietary source of iodine in the UK and Ireland. Methods We surveyed the iodine status of 903 girls aged 14-15 years in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…Neither the UK nor Ireland has ever had a salt iodisation policy, with dietary iodine relying heavily on adventitious intakes, particularly from dairy produce where presence of iodine in cleaning solutions or in animal feed has historically led to iodine entering milk and dairy produce (2,3). Without any iodised salt policy, a number of studies have investigated iodine intake and status in UK and Irish populations, suggesting some concern (4)(5)(6)(7)(8). This against a background where there has been a rise in non-dairy milk alternatives which may not contain iodine (9).…”
Section: Introductionmentioning
confidence: 99%
“…Neither the UK nor Ireland has ever had a salt iodisation policy, with dietary iodine relying heavily on adventitious intakes, particularly from dairy produce where presence of iodine in cleaning solutions or in animal feed has historically led to iodine entering milk and dairy produce (2,3). Without any iodised salt policy, a number of studies have investigated iodine intake and status in UK and Irish populations, suggesting some concern (4)(5)(6)(7)(8). This against a background where there has been a rise in non-dairy milk alternatives which may not contain iodine (9).…”
Section: Introductionmentioning
confidence: 99%
“…Mullan et al also reported that concentration of iodine in milk is higher in the winter than in the summer. Additionally, urinary iodine concentration among girls was lower in summer than winter and was positively correlated with milk consumption [53]. In fact, there are differences between iodine concentrations in milk between various regions in the winter and in the summer which suggest that iodine concentration is dependent on feeding [54].…”
Section: Food Sources Of Iodinementioning
confidence: 93%
“…Cow's milk intake has been in decline over the last 50 years and intake amongst females women, children and teenagers is especially low 18,19,28,53 . A consistent dose‐dependent relationship has been demonstrated between iodine status and milk and dairy intake among females teenage girls in the UK 18,19 . The WHO recommends an intake of 250 µg iodine in pregnancy and one pint of cow's milk (560 mL) equates to approximately 140–224 µg of iodine (Figure 1).…”
Section: Changes In Dietary Preferences and The ‘Post‐milk’ Eramentioning
confidence: 97%
“…The SACN in their 2014 position paper noted that teenage girls, milk and fish avoiders and vegans may be at particular risk of iodine deficiency 16 . In 2015, an all‐Ireland survey of 900 teenage girls demonstrated a levels in the low sufficiency range mUIC of 111 μg/L 19 . The most recent UK National Diet and Nutrition Survey (NDNS) based on 2016–2018 data found that the mUIC for women aged 16–49 years ( n = 426) was borderline normal at 102 µg/L with 17% of that population <50 µg/L 20 .…”
Section: British Isles Iodine Status In the 21st Cmentioning
confidence: 99%